Mitochondrial tRNA methylation in Alzheimer's disease and progressive supranuclear palsy - Talisa K. Silzer; Gita A. Pathak; Nicole R. Phillips (BMC, 2020)
Abstract Background Methylation of mitochondrial tRNAs (mt-tRNA) at the 9th position ("p9 site") is known to impact translational efficiency and downstream mitochondrial function; however, direct assessment of mt-RNA methylation is challenging. Recent RNA sequence-based methods have been developed to reliably identify post-transcriptional methylation. Though p9 methylation has been studied in healthy human populations and in the context of cancer, it has not yet been analyzed in neurodegenerative disease, where mitochondrial dysfunction is a prominent and early hallmark of disease progression. Methods Mitochondrial p9 methylation was inferred from multi-allelic calls in RNA-seq data. Gene-based association studies were performed in FUMA. Correlations between nuclear gene expression and p9 methylation were tested using Spearman's rho. Fisher's Exact test was used in PANTHER and IPA to test for overrepresentation and enrichment of biological processes and pathways in the top nuclear genes correlated with p9 methylation. Results Variable methylation was observed at 11 p9 sites in post-mortem cerebellar tissue of elderly subjects who were either healthy or diagnosed with Alzheimer's disease (AD), progressive supranuclear palsy (PSP) or pathological aging (PA). Similarities in degree of methylation were observed between AD and PSP. Certain nuclear encoded genes were identified as significantly associated with p9 methylation. Expression of 5300 nuclear encoded genes was significantly correlated with p9 methylation, with AD and PSP subjects exhibiting similar expression profiles. Overrepresentation and enrichment testing using the top transcripts revealed enrichment for a number of molecular processes, terms and pathways including many of which that were mitochondrial-related. Conclusion With mitochondrial dysfunction being an established hallmark of neurodegenerative disease pathophysiology, this work sheds light on the potential molecular underpinnings of this dysfunction. Here we show overlap in cerebellar pathophysiology between common tauopathies such as Alzheimer's disease and progressive supranuclear palsy. Whether p9 hypermethylation is a cause or consequence of pathology remains an area of focus.